Vortical electron dynamics in plasma, observed at interaction of laser pulse with foil - Maslov, V.I.; Yegorov, A.M.; Onishchenko, I.N.; Suhostavez, O.V. (Вопросы атомной науки и техники, 2009)
The distribution of electrical potential and electron density near foil, resulting in vortical electron dynamics at interaction of an intensive laser pulse with a foil, is considered.